Sustainability in Corporate Practice Certification Based on DIN and ISO (European Journal of Marketing and Economics, 2024)
The term sustainability is increasingly evolving as a buzzword and is frequently used in a manner which is different to its original meaning. Building upon the triple bottom line discussion one can however ascertain that the current social, ecological and economic challenges represent fundamental issues for the corporate context. In this manner it is a matter of business sustainability (BST)/ "Corporate Sustainability" (CS) and the significance for "Sustainable Development" (SD) in an enterprise. SD can therefore be an expression of ethical thinking and conduct within an enterprise which means that sustainability should be embedded firmly in corporate strategies and role models and must be the object of all forms of corporate/political decision-making. In this manner a company meets the requirements of so-called sustainability ethics which represents a combination of ethical thoughts and sustainable objectives. In this regard certification in the company based on the German industrial norm (DIN)/ the instructions of the International Standard Organization (ISO) can help to ensure the implementation of sustainability in the company. However, these activities cannot merely be ticking off checklists but must be implemented in the context of the corporate culture.
Keywords: Sustainability, Certification, Ethics, Management, Corporate Management